Analisis Digital Marketing dalam Pendapatan Hotel Fame Gading Serpong - Christopher Deo; Gabriel Wira; Satria Putranto; Dyah Cahyasari (Yayasan Literasi Sains Indonesia, 2023)
Digital marketing is experiencing revolutionary changes along with technological developments in the digital era. This research aims to analyze the impact of digital marketing strategies on the income of the Fame Gading Serpong Hotel, Tangerang Regency. In the context of significant transformation in the hotel industry due to technology and changing consumer trends, this research identifies the strategic role of digital marketing in increasing the competitiveness of Hotel Fame Gading Serpong. This research method uses a qualitative approach with a focus on documentation, interviews and digital marketing analysis at the hotel. Data was collected through interviews with hotel management and visitors who are experienced in digital marketing. Purposive sampling technique was used to select samples that provide in-depth insight into digital marketing strategies. The aim of this research is to analyze the income of the Fame Gading Serpong Hotel generated through digital marketing, as well as exploring the effectiveness of this strategy in attracting visitors. This research also aims to provide practical guidance for similar hotels in implementing digital marketing strategies that are efficient and responsive to market changes. The research results show that Hotel Fame Gading Serpong has successfully implemented an integrated digital marketing strategy, involving social media, official website and online campaigns. The positive impact can be seen in increasing awareness and the number of visitors, which in turn contributes to increasing hotel revenue.